Developmental trajectories of expert perception processing of Chinese characters in primary school children - Yini Sun; Jianping Wang; Qing Ye; Baiwei Liu; Ping Zhong; Chenglin Li; Chenglin Li; Xiaohua Cao; Xiaohua Cao (Frontiers in Psychology, 2022)
Previous studies have demonstrated that inversion effect and left-side bias are stable expertise markers in Chinese character processing among adults. However, it is less clear how these markers develop early on (i.e., among primary school students). Therefore, this study aimed to investigate the development of the two markers by comparing primary school-aged students of three age groups (Grade 1, Grade 3, and Grade 5) and adults in tests of inversion effect (Experiment 1) and left-sided bias effect (Experiment 2). The results replicated that both effects during Chinese character processing were present among adults. However, more importantly, the effects were different among primary school-aged students in different grades: the inversion effect was found as early as in Grade 1, but the left-side bias effect did not emerge in Grade 1 and as approximated that of adults until Grade 3. The study suggested a potential dissociation in developing different aspects of expertise during Chinese character processing in early childhood.